Undifferentiated pleomorphic sarcoma of maxilla - Rezhat Abbas; Suheel Hamid Latoo; Mohammad Shafi Dar; Afreen Nadaf (Saudi Journal of Oral Sciences)
Undifferentiated pleomorphic sarcoma (UPS) formerly known as malignant fibrous histiocytoma is a high-grade aggressive soft-tissue sarcoma. UPS is a soft-tissue sarcoma without a definable line of differentiation. Men between the ages of 50 and 70 are frequently affected by it. In adults, the lower extremity and retroperitoneum are the most affected sites, while the paranasal sinus is affected in younger individuals. A 16-year-old male patient reported with swelling in his left posterior maxilla for 2 months. The swelling began quickly and gradually expanded to its current size. On examination, an ill-defined, deep-seated exophytic, ovoid growth was seen on the left maxillary alveolus. Histopathological findings indicated UPS. UPS is a rare malignancy that typically originates in the body’s soft tissues. The treatment for UPS is determined on the site of the cancer, but it typically includes surgery and radiation.